The Perceptions of Peter and Lucy Towards Aslan’s Absence and Its Impact in The Chronicles of Narnia: Prince Caspian - Gabriella Alma Gunawan; Liliek Soelistyo (Kata Kita: Journal of Language, Literature, and Teaching, 2025)
In this thesis, I chose the movie titled The Chronicles of Narnia: Prince Caspian as my object of analysis. I choose this movie because it portrays the world of Narnia without Aslan. The topics addressed in this thesis are how Peter and Lucy perceive Aslan’s and how their perceptions affect their way of thinking. I use the perceptual cycle theory by Neisser (1976) which shows the process of perception and its impact on the decision-making process of Peter and Lucy. The findings of the analysis are that Peter and Lucy have different perceptions of Aslan’s absence because of the information modification in the schemata. Moreover, the analysis shows the impact of Peter’s and Lucy’s perceptions to their way of thinking in making choices. In conclusion, this analysis proves the importance of evaluating perception because of the danger it poses to one’s way of thinking in making a choice.